2017
DOI: 10.1175/jcli-d-16-0536.1
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Recent and Future Temperature Change over the Sichuan Basin, China, Using CMIP5 Climate Models

Abstract: The Sichuan basin is one of the most densely populated regions of China, making the area particularly vulnerable to the adverse impacts associated with future climate change. As such, climate models are important for understanding regional and local impacts of climate change and variability, like heat stress and drought. In this study, climate models from phase 5 of the Coupled Model Intercomparison Project (CMIP5) are validated over the Sichuan basin by evaluating how well each model can capture the phase, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 66 publications
3
29
0
Order By: Relevance
“…Similar results also been shown by Huang et al [35] that the CMIP5 GCMs underestimated the annual mean surface air temperature relative to the Climate Research Unit temperature data (CRU TS 3.21) in Mekong River Basin. Other study in monsoon region of Sichuan Basin conducted by Bannister et al [17] showed that mean temperature was underestimated by CMIP5 GCMs, especially during the winter, with bias exceeding −3 • C. Furthermore, another study in the Qinghai-Tibetan Plateau also showed that CMIP5 GCMs underestimated annual and seasonal temperatures, with bias at −2.3 • C for the annual mean, and larger cold biases for autumn and winter [47]. However, a study by Miao et al [5] showed that most of the CMIP5 GCMs overestimated the annual mean surface air temperature in Northern Eurasia, especially during the winter.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similar results also been shown by Huang et al [35] that the CMIP5 GCMs underestimated the annual mean surface air temperature relative to the Climate Research Unit temperature data (CRU TS 3.21) in Mekong River Basin. Other study in monsoon region of Sichuan Basin conducted by Bannister et al [17] showed that mean temperature was underestimated by CMIP5 GCMs, especially during the winter, with bias exceeding −3 • C. Furthermore, another study in the Qinghai-Tibetan Plateau also showed that CMIP5 GCMs underestimated annual and seasonal temperatures, with bias at −2.3 • C for the annual mean, and larger cold biases for autumn and winter [47]. However, a study by Miao et al [5] showed that most of the CMIP5 GCMs overestimated the annual mean surface air temperature in Northern Eurasia, especially during the winter.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, Hawkins and Sutton [16] suggested that model uncertainty was more important than internal variability for decadal time scales and regional spatial scales (~2000 km). Therefore, a GCM that can simulate observed temperature reasonably well should be selected before a climate change projection is made [5,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that the global climate models are useful tools for investigating climate change, we utilized the CMIP5 models to reveal the key role of DMO in SAT. Note that multi-model ensemble strategy is traditionally used to exploit the diversity of skilful predictions by different models (Xu and Xu, 2012;Zhang, 2012), but this method does not consider the relative strength and weakness of each model as an ensemble invariably hides the substantial variation among individual models (Bannister et al, 2017). In addition, the internal variability of different models might be offset or strengthened through ensemble mean.…”
Section: Resultsmentioning
confidence: 99%
“…The CMIP5 experiments (Taylor et al, 2011) include simulations of 20th-century climate (referred as historical experiments) and of 21st-century climate under new greenhouse gas emission scenarios (referred as representative concentration pathways [RCPs]; Meinshausen et al, 2011). The RCPs represent different emission pathways according to assumed policy decisions, which would influence the future emissions of greenhouse gases, aerosols, ozone, and land-use changes (Bannister et al, 2017). In this study, the outputs for temperature from the historical simulations of 19 models were selected (Table 1), together with their RCP4.5 outputs runs from 2005 to 2015, to compare with the observational data set.…”
Section: Data Sourcesmentioning
confidence: 99%
“…These studies all demonstrate that understanding and gauging the uncertainty of GCMs is especially crucial for future projections of climate change, which is a widely discussed and acknowledged subject (Hawkins & Sutton, 2011;Najafi et al, 2011). Therefore, it is imperative to continue assessments of GCM performance, in order to provide reliable projections on future climate patterns (Bannister et al, 2017;Miao et al, 2014).…”
Section: Introductionmentioning
confidence: 96%